The Euphoria Effect of UEFA Champion League Final on Asian Stock Market - Brahmana, Rayenda Khresna (Canadian Center of Science and Education, 2011)
Football is the most popular sport in the world. It can make personal attachment to the supporters. One of the most wanted football events is UEFA Champion League Final. It can create euphoria in the supporters. The euphoria will affect the stock market behaviour. This research examines whether investor’s performance affected by the football euphoria. This research is important in term of market efficiency, behavioural finance, and portfolio strategy.